Pengembangan Ilmu Hukum di Indonesia: Reformasi dalam Penyelesaian Permasalahan Hukum - Ismansyah, Ismansyah; Muchtar, Henni (Jurnal Demokrasi, 2010)
This article will discuss the reform of law in Indonesia, especially that of related to law conflict resolution. Law is a complex system. Linkages between the elements can not be separated. Law is not just the law. The law is not always a command of the State authorities. Law is the result of social forces and means of social control. On the other side, politics often intervene on the act and the implementation of the law. Law can be viewed and studied from various angles. The inability of law in addressing social problems outside the law will result in the authority of the law itself. Kata Kunci: law, legal problems, the development of legal science, legal reform